Leontief Input-Output Method for The Fresh Milk Distribution Linkage Analysis - Istiqomah, Riski Nur; Fayeldi, Trija (CAUCHY, 2016)
This research discusses about linkage analysis and identifies the key sector in the fresh milk distribution using Leontief Input-Output method. This method is one of the application of Mathematics in economy. The current fresh milk distribution system includes dairy farmers →collectors→fresh milk processing industries→processed milk distributors→consumers. Then, the distribution is merged between the collectors’ axctivity and the fresh milk processing industry. The data used are primary and secondary data taken in June 2016 in Kecamatan Jabung Kabupaten Malang. The collected data are then analysed using Leontief Input-Output Matriks and Python (PYIO 2.1) software. The result is that the merging of the collectors’ and the fresh milk processing industry’s activities shows high indices of forward linkages and backward linkages. It is shown that merging of the two activities is the key sector which has an important role in developing the whole activities in the fresh milk distribution.